Assembly and Breakup of Rodinia(Some Results of IGCP Project 440) - Bogdanova , S.; Pisarevsky, S.; Li, Zheng-Xiang (Maik Nauka/Interperiodica/Springer, 2009)
The principal results of project 440 'Assembly and Breakup of Rodinia' of the International Geological Correlation Programme (IGCP) are reviewed in this work. A map of that supercontinent compiled using geological and paleomagnetic data describes global paleogeography 900 Ma ago. The assembly of Rodinia, which comprised most of Precambrian continental blocks, lasted ca. 400 m.y. (from 1300 to 900 Ma). Its breakup presumably triggered by mantle superplume took place between 830 and 650 Ma. The correlation between tectonic events in different continental blocks is considered. Some problems concerning the Rodinia reconstruction and history, e.g. the slow growth of juvenile crust and effects of mantle-plume events during the amalgamation period and of glaciations at the breakup time, are discussed. The latter caused changes in the biosphere and climate, whereas post glacial periods stimulated progress in biota evolution.